Benefits of ultra-fast-track anesthesia in left ventricular assist device implantation: a retrospective, propensity score matched cohort study of a four-year single center experience. Issue 1 (December 2017) - Zayat, Rashad; Menon, Ares; Goetzenich, Andreas; Schaelte, Gereon; Autschbach, Ruediger; Stoppe, Christian; Simon, Tim-Philipp; Tewarie, Lachmandath; Moza, Ajay
Abstract Background The use of left ventricular assist devices (LVADs) has gained significant importance for treatment of end-stage heart failure. Fast-track procedures are well established in cardiac surgery, whereas knowledge of their benefits after LVAD implantation is sparse. We hypothesized that ultra-fast-track anesthesia (UFTA) with in-theater extubation or at a maximum of 4 h. after surgery is feasible in Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) level 3 and 4 patients and might prevent postoperative complications. Methods From March, 2010 to March, 2012, 53 LVADs (50 Heart Mate II and 3 Heart Ware) were implanted in patients in our department. UFTA was successfully performed (LVADultra ) in 13 patients. After propensity score matching, we compared the LVADultra group with a matched group (LVADmatch ) receiving conventional anesthesia management. Results Patients in the LVADultra group had significantly lower incidences of pneumonia (p  = 0.031), delirium (p  = 0.031) and right ventricular failure (RVF) (p  = 0.031). They showed a significantly higher cardiac index in the first 12 h. (p  = 0.017); a significantly lower central venous pressure during the first 24 h. postoperatively (p  = 0.005) and a significantly shorter intensive care unit (ICU) stay (p  = 0.016). Kaplan-Meier analysis after four years of follow-up showed no significant difference in survival. Conclusion In this pilot study, we demonstrated the feasibility of ultra-fast-track anesthesia in LVAD implantation in selected patients with INTERMACS level 3–4. Patients had a lower incidence of postoperative complications, better hemodynamic performance, shorter length of ICU stay and lower incidence of RVF after UFTA. Prospective randomized investigations should examine the preservation of right ventricular function in larger numbers and identify appropriate selection criteria.